Respuesta :
The Answer is c: 5r+12
Proof:
Simplify the following:
2 (3 r + 7) - (r + 2)
2 (3 r + 7) = 6 r + 14:
6 r + 14 - (r + 2)
-(r + 2) = -r - 2:
14 + 6 r + -r - 2
Grouping like terms, 14 + 6 r - 2 - r = (6 r - r) + (14 - 2):
(6 r - r) + (14 - 2)
6 r - r = 5 r:
5 r + (14 - 2)
| 1 | 4
- | | 2
| 1 | 2:
Answer: 5 r + 12
Proof:
Simplify the following:
2 (3 r + 7) - (r + 2)
2 (3 r + 7) = 6 r + 14:
6 r + 14 - (r + 2)
-(r + 2) = -r - 2:
14 + 6 r + -r - 2
Grouping like terms, 14 + 6 r - 2 - r = (6 r - r) + (14 - 2):
(6 r - r) + (14 - 2)
6 r - r = 5 r:
5 r + (14 - 2)
| 1 | 4
- | | 2
| 1 | 2:
Answer: 5 r + 12
Hey there! :) The easiest way to find an expression equivalent to our given one, we can very simply simplify the given expression.
2(3r + 7) - (2 - r)
Simplify.
6r + 14 - 2 - r
Add like terms.
(6r - r) + (14 - 2)
Simplify.
5r + 12
Look at our given answer choices.
Our answer is c. 5r + 12
~Hope I helped!~
2(3r + 7) - (2 - r)
Simplify.
6r + 14 - 2 - r
Add like terms.
(6r - r) + (14 - 2)
Simplify.
5r + 12
Look at our given answer choices.
Our answer is c. 5r + 12
~Hope I helped!~